PENGARUH KOTORAN JANGKRIK TERHADAP PERTUMBUHAN TIGA JENIS TANAMAN FAST GROWING - , RIKA BELA RAHMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Every plant in the growth and development need nutrients, both macro and micro, therefore if the plant has a limited nutrition, it will make stunted growth. The stunted growth can be overcome by the fertilization. The importance of fertilizer makes the most of the public need a lot of fertilizer and it is needed to their plant. Lately, there are business lands that take advantage of crickets especially in big cities such as Bekasi. Utilization of manure waste into organic fertilizer crickets into potential along with the need for fertilizers is increasing. This research aims to determine the effect of impurities crickets on the growth of seedlings Sengon laut (Paraserianthes falcataria), Sengon buto (Enterolobium cyclocarpum), and Lamtoro (Leucaena leucocephala) and also knowing the chemical content of nutrients in the stool of crickets. This research was conducted in the Laboratory of Intensive Silviculture Faculty of Forestry, Klebengan, Sleman, Yogyakarta. The method used the measurement of growth parameters include the height, diameter, and survival rate at 3 different types of fast growing seedlings in Sengon laut, Sengon buto, and Lamtoro. Measurements were taken once a week during 10 weeks, from October 2013 to January 2014. This research uses a series of CRD with three fertilizer treatments, by comparison of the dirt ground crickets